Lymphoma : diagnosis and treatment - Coiffier, Bertrand; Younes, Anas (Current Clinical Oncology, 2013)
Recently, understanding the molecular pathogenesis of malignant lymphomas has led to improvement in the diagnostic precision and to the identification of a variety of molecular therapeutic targets. In addition, new drugs have been approved in the US and Europe, resulting in changes in the standard of care of several types of lymphoid malignancies. Comprehensive in scope and developed by a team of internationally renowned authors, Lymphoma: Diagnosis and Treatment provides a timely update on the most important advances in the biology, diagnosis, and therapy of lymphomas. As part of the Current Clinical Oncology series, Lymphoma: Diagnosis and Treatment will be of value to medical oncologists, hematologists, radiation oncologists, and all physicians involved in the care of patients with lymphoid malignancies.